Pendidikan Karakter dan Pembangunan Desa Berkelanjutan: Mendukung Agenda SDGs Melalui Penanaman Nilai-nilai Pancasila - Fauziyah Fauziyah; Bina Ridha Kusumaningtyas; Pramukhtiko Suryo Kencono (Journal of Community Development, 2024)
Sustainable development has become an urgent global agenda, with the Sustainable Development Goals (SDGs) serving as a key guide for these efforts. However, in the village context, the implementation of the SDGs often requires a different approach that takes into account the unique characteristics of rural communities. The purpose of this article is to discuss the character values of Pancasila that provide a strong foundation for realizing sustainable rural development in line with the SDGs. By strengthening Pancasila principles such as gotong royong, social justice, and unity, rural communities can accelerate the achievement of development goals related to welfare, environment, and social inclusion. The method of community service is through socialization to students of State Elementary School 01 Sumberjati Lumajang as future leaders in the village. The results of this community service are expected that the students of State Elementary School 01 Sumberjati Lumajang can integrate the values of Pancasila in every stage of planning and implementing village development programs, so that the role of the village functions as a center of innovation and sustainability, not only for local interests, but also as a valuable contributor to the achievement of SDGs globally. to achieve sustainable development, village communities can adopt environmentally friendly practices in their daily activities starting from the students of State Elementary School 01 Sumberjati Lumajang, for example in the management and sorting of organic and inorganic waste, the use of renewable energy, and organic farming. As well as promoting awareness of the importance of environmental conservation through education and environmental campaigns at the local level.